Approach to Lower Urinary Tract Reconstruction: A Survey of Adult and Pediatric Urologist Perspectives and Experiences - Lembrikova, Katerina; Aninwene, George; Christensen, Katherine L.; Tandel, Megha; Kwan, Lorna; Gonzalez-Padilla, Daniel; Teoh, Jeremy; Sturm, Renea (Frontiers in Urology, 2022)
Introduction Robotic adoption has rapidly increased within urology. Initial uptake in adult urology has outpaced that seen in pediatric procedures. The aim of this study was to determine adult and pediatric urologist satisfaction with specific procedural steps in lower urinary tract reconstruction (LUTR) using an open versus robotic approach and define drivers and barriers to robotics adoption to inform device development relevant to current needs. Methods A survey was distributed to practicing urologists. Questions assessed surgeon demographics, technology adoption, satisfaction with anastomotic steps in continent neobladder (CN) and augmentation cystoplasty (AC), and drivers/barriers influencing robotic use. Results Of 110 respondents, 49% practiced in academic institutions; 51% reported non-academic, private, or other. Specializations were pediatrics (36%), oncology/robotics (25%), or other (39%). Sixty-eight percent completed training in the past decade. In the past year, 55% completed only open CN or AC, 36% only robotic, and 9% both. Of those that performed robotic procedures, 5% used only an intra-corporeal approach, 85% used only extra-corporeal, and 10% used both. Surgeons who performed robotic LUTR alone expressed high satisfaction with all CN and AC procedural steps evaluated. Overall, of the anastomoses evaluated, urologists found urethrovesical anastomoses more satisfactory using a robotic versus open approach. Pediatric versus adult urologists were overall less satisfied with the robotic approach. In terms of robotic adoption, major drivers for CN were adoption by neighboring institutions, improved perioperative outcomes, and equivalent oncological outcomes; barriers were cost of robotic purchase and maintenance, surgeon support for robotics, and difficult learning curve. Major drivers for AC were adoption by neighboring institutions, decreased operative time, and equivalent oncological outcomes; barriers were increased operative time, cost, and minimal perceived benefit of extracorporeal procedures. Conclusion Urologic oncologists and surgeons performing robotic LUTR alone were highly satisfied with the robotic approach. Pediatric urologists reported lower overall satisfaction with robotic steps in LUTR, potentially corresponding with limitations of current robotic platforms for pediatric application and relative training exposure. Major drivers overall were competition and outcomes; major barriers were cost, operative time, and learning curve. Based on this select surgeon cohort recruited through targeted social media platforms, maximizing surgeon experience through training and innovations to reduce complication rates is anticipated to facilitate broader adoption of robotics in LUTR. Future studies that include a broad international distribution across the specialty may further pinpoint specified needs for adult versus pediatric specialists and drive targeted robotics platform development.